Implementasi Kebijakan Tentang Penciptaan Budaya dan Iklim yang Kondusif pada SDIT Insan Kamil Bangkinang Kota: Kebijakan Pendidikan - Muhammad Ibnu Haikal, Ibnu (JURNAL ISLAMIKA, 2024)
Effective, efficient, and productive school development needs to be supported by changes in various aspects related to education, including the school climate. Changes in school climate need to be carried out to respond to the deteriorating condition of education. A conducive school climate and culture is characterized by the creation of a safe, comfortable and orderly learning environment so that learning can take place effectively. The principal becomes a determining part of the realization of a good school culture on the basis of the policies implemented, the programs launched, as well as clear targets and strategies for achieving them. Regarding the creation of culture and climate, the principal of SD IT Insan Kamil Bangkinang Kota prepares planning, Organizing, leadership, and controlling.